Continuous palliative sedation until death: a qualitative study of palliative care clinicians’ experiences - Guité-Verret, Alexandra; Boivin, Jessica; Hanna, Andrew M. R.; Downar, James; Bush, Shirley H.; Marcoux, Isabelle; Guay, Diane; Tapp, Diane; Lapenskie, Julie; Gagnon, Bruno (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background The practice of continuous palliative sedation until death is the subject of much medical and ethical debate, which is reflected in the inconsistency that persists in the literature regarding the definition and indications of palliative sedation. Aim This study aims to gain a better understanding of palliative care clinicians’ experiences with continuous palliative sedation. Design We conducted a qualitative study based on focus group discussions. Setting/participants We conducted six focus groups with a total of 28 palliative care clinicians (i.e., 15 nurses, 12 physicians, and 1 end-of-life doula) from diverse care settings across Canada, where assisted dying has recently been legalized. Results An interpretative phenomenological analysis was used to consolidate the data into six key themes: responding to suffering; grappling with uncertainty; adapting care to ensure ongoing quality; grounding clinical practice in ethics; combining medical expertise, relational tact, and reflexivity; and offering an alternative to assisted death. Conclusions Interaction with the patient’s family, uncertainty about the patient’s prognosis, the concurrent practice of assisted dying, and the treatment of existential suffering influence the quality of sedation and indicate a lack of clear palliative care guidelines. Nevertheless, clinicians exhibit a reflective and adaptive capacity that can facilitate good practice.